The politics of equity finance in emerging markets - Lavelle, Kathryn C. (Oxford University Press, 2004)
Kathryn C. Lavelle uses a political science paradigm to explain the growth of emerging equity markets. She departs from conventional economic explanations and examines politics at the micro-level of large issues of emerging market stock.